Les espaces de fabrication et d’expérimentation numérique sont-ils des tiers-lieux ? - Flavie Ferchaud; Marc Dumont (Territoire en Mouvement)
The concept of third place is seductive and can be applied to any kind of places. It is updated following the generalization of the use of ICT in the society. However, the spatial and territorial dimension of third places focused on digital practices is not yet approached by researchers. Our paper tackles this dimension. Fablabs emerged in 2004 in a normalized environment at the Massachussetts Institute of Technology (MIT) but recent studies showed differences between local implementation and the initial model. In France, fablabs are being integrated by public policies and are pushed to be part of the national and local economic development through incentives. Fablabs in Rennes and Toulouse (France) are investigated with focuses on digital fabrication and experimentation places. In Rennes, the Labfab is a territorial and institutional network of fablabs. Rennes strategy contrasts with the national incentives but it is going to be normalized. In Toulouse, Artilect anticipated the incentives but kept a strong collective dimension. The two study cases give avenues for reflection about Internet and territory's spatial logics. Fablabs finally help to think again the “enchanted” dimensions of the third place as defined by R. Oldenburg (1999).